White adipocyte-targeted dual gene silencing of FABP4/5 for anti-obesity, anti-inflammation and reversal of insulin resistance: Efficacy and comparison of administration routes. (December 2021) - Chung, Jee Young; Hong, Juhyeong; Kim, Hyung-Jin; Song, Yoonsung; Yong, Seok-Beom; Lee, Jieun; Kim, Yong-Hee
Abstract: Obesity is a serious health problem with tremendous economic and social consequences, which is associated with metabolic diseases and cancer. Currently available anti-obesity drugs acting in the gastrointestinal tract, or the central nervous system have shown limited efficacy in the reduction of obesity, accompanied by severe side effects. Therefore, a novel therapeutic delivery targeting adipocytes and normalizing excess fat transport and accumulation is necessary to maximize efficacy and reduce side effects for long-term treatment. Fatty acid binding protein 4 (FABP4) is an adipokine that coordinates lipid transport in mature adipocyte and its inhibition in obesity model showed weight loss and normalized insulin response. Reduction of FABP4 level in adipocytes was compensated by fatty acid binding protein 5 (FABP5), which resulted in reduction of recovery of obesity and co-morbidities related to obesity by FABP4 knock-down alone. In this study, we developed a non-viral gene delivery system, sh (FABP4/5)/ATS9R, that silences FABP4 and FABP5 simultaneously with oligopeptide (ATS9R) that can selectively target mature adipocyte. For future clinical application to increase patient compliance, sh (FABP4/5)/ATS9R was administered subcutaneously and intraperitoneally to obese animal model and both routes demonstrated startling dual gene efficacy in visceral adipose tissues. Furthermore, dual gene silencing efficiently alleviated obesity, improved insulin sensitivity and restored hepatic metabolism in high fat diet-induced type 2 diabetes mouse model. Targeted-dual gene silencing of sh (FABP4/5)/ATS9R in adipose tissues demonstrated synergistic effects to overcome obesity and obesity-induced metabolic diseases and beneficial effects against liraglutide, providing a great potential for future translational research. Graphical abstract: Image 1